Fatores que interferem a autoimagem genital de idosas - Tavares, Deise Iop (2020)
This master's thesis has genital self-image as its central theme. Genital self-image consists of the identity of the genitalia in its personal representation, which can interfere with attitudes and choices that are related to sexuality. This study aimed to verify which are the main factors that interfere with the genital self-image of elderly women. Initially, it was investigated in the literature which factors interfere and the following factors are listed: age, marital status, body image, pelvic floor dysfunctions such as urinary incontinence and pelvic organ prolapse. Still, the aesthetic surgeries on the genitalia, sexual function and the frequency of sexual activity were listed. The study consisted of an explanatory and retrospective quantitative research, with 132 elderly women from a city in the interior of Rio Grande do Sul, registered in the Integrated Center for Study and Support for the Elderly (NIEATI). To participate in the study, they must be 60 years of age or older and sexually active. Women with cognitive impairment and with any active self-reported genital pathology were excluded. The instruments used were the Mini-Mental State Examination (MMSE) to assess cognition, an Adapted Assessment Form to investigate sociodemographic data as well as gynecological and obstetric antecedents. The Female Sexual Function Index (FSFI) questionnaire was also used to investigate sexual function and the Female Genital Self - Image Scale (FGSIS) questionnaire to assess genital self-image. Body image was investigated using the Body Appreciation Scale (BAS) questionnaire and to assess urinary incontinence, the International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF). For the static analysis, a multicollinearity analysis was performed in which all variables showed tolerance greater than 0.1 and VIF less than 10, followed by binary logistic regression by the likelihood stepwise forward method, to verify whether the factors are predictors of discontent with the genital image (FGSIS <21.8). As a result, it was noticed that the sample had a positive genital self-image and it was found that only the body image (BAS) was significant [X² (1) = 17.909; p <0.001, R²Negelkerke = 0.214, OR = 8.552; 95% CI 2.72- 26.84]. Age (p = 0.618), marital status (p = 0.931), urinary incontinence (p = 0.685) and pelvic prolapse (p = 0.454), cosmetic surgery on the genitalia (p = 0.908), sexual function (p = 0.369) and frequency of sexual activity in the last month (p = 0.106) did not interfere with the genital self-image of the elderly women studied. It is concluded that the genital self-image is influenced by the way the elderly view their body and this can interfere with health and sexual issues.